English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-02-19 16:43:28 · 4 answers · asked by lirael1019 1 in Science & Mathematics Mathematics

4 answers

Howdy! :)

I sure hope you're doing well. :) As for the exercise:

3 -- 22/(x+5)= (6x+1)/(2x+7)

First, simplify the left side by creating a common denominator:

3 -- 22/(x+5)= [3(x + 5) -- 22]/(x + 5)= (3x + 15 -- 22)/(x + 5)=
(3x -- 7)/(x + 5).

Now the original expression looks like this:

(3x -- 7)/(x + 5) = (6x+1)/(2x+7)

Now cross-multiply: multiply the numerator of the left side by the denominator of the right side. And multiply the numerator of the right side by the denominator of the left side. As follows:

(3x -- 7)(2x+7) = (6x+1)(x + 5)

Now simplify by multiplying the terms of the brackets for both sides:

6x^2 + 21x -- 14x -- 49 = 6x^2 + 30x + x + 5

Now bring all the x terms to the left side and the numbers to the right side and all the terms on both sides:

-- 24x = 54

(6x^2 -- 6x^2 + 21x -- 14x -- 30x -- x = 49 + 5)

Now divide both by -- 6. You get:

4x = -- 9

Finally, divide both sides by 4 and that's the answer:

x = -- 9/4


I sure hope this helps. :) Good luck, take care and have a great day. :)

Cheers! :)

2007-02-19 19:52:18 · answer #1 · answered by Cogano 3 · 0 0

assuming expression is two/(x+5) - 3/(2x+a million) = 5/(6x+3) completely aspect 2/(x+5) - 3/(2x+a million) = 5/3(2x+a million) be conscious that our LOWEST undemanding denominator is 3(x+5)(2x+a million): 3(2x+a million)(2)/3(x+5)(2x+a million) - 3(x+5)(3)/3(x+5)(2x+a million) = (x+5)(5)/3(x+5)(2x+a million) DROP denominators and make certain utilising numerators 3(2x+a million)(2) - 3(x+5)(3) = (x+5)(5) 6(2x+a million) - 9(x+5) = 5(x+5) 12x + 6 - 9x - 40 5 = 5x + 25 3x - 39 = 5x + 25 5x - 3x = -39 - 25 2x = -sixty 4 2x/2 = -sixty 4/2 x = -32 ?(3x+a million) - ?(x+4) = a million sq. both aspect (?(3x+a million) - ?(x+4))^2 = (a million)^2 ?(3x+a million)^2 - ?(3x+a million)(x+4) - ?(3x+a million)(x+4) + ?(x+4)^2 = a million 3x + a million - 2?(3x+a million)(x+4) + x + 4 = a million 4x + 5 - 2?(3x+a million)(x+4) = a million 4x + 5 - a million = 2?(3x+a million)(x+4) 4x + 4 = 2?(3x+a million)(x+4) divide both aspect through 2 2x + 2 = ?(3x+a million)(x+4) sq. both aspect (2x+2)^2 = (?(3x+a million)(x+4))^2 4x^2 + 4x + 4x + 4 = (3x+a million)(x+4) 4x^2 + 8x + 4 = 3x^2 + x + 12x + 4 4x^2 + 8x + 4 = 3x^2 + 13x + 4 4x^2 - 3x^2 + 8x - 13x + 4 - 4 = 0 x^2 - 5x = 0 x(x-5) = 0 x=0 and (x-5)=0 x=0 and x = 5

2016-12-04 09:58:30 · answer #2 · answered by ? 4 · 0 0

1) Cross multiply the denominirators.
2) Equalize & then slove further.

2007-02-19 17:13:52 · answer #3 · answered by Archu 2 · 0 0

cross multiply and you'll get the answer!

2007-02-19 16:51:32 · answer #4 · answered by someone [: 2 · 0 0

fedest.com, questions and answers